Modelling of Piled Raft Foundation on Soft Clay (University of Khartoum Engineering Journal, 2022)
This study relates to the analysis of un – piled and piled raft foundations with soft clay soil conditions.The subsoil model was assumed uniform underneath the foundation with soil stiffness increasing with depth.Based on these variables a finite element analysis was conducted on un – piled and piled raft foundation. For theun – piled raft, a 8m × 8m raft size with variable thickness varying from0.25m, 0.4m, 0.8m and 1.5m wereconsidered in this study. As for the piled raft, first, an 8m × 8m piled raft size with thickness that varies from0.25m, 0.4m; 0.8m and 1.5m were considered. Secondly, a piled raft with raft thickness of 0.8m, while the pilesspacing is varied as 3d, 4d, 5d, 6d and 7d were considered. The piles are 0.7m diameter and 16m length. For theaforementioned examples; walls were involved in the analysis to study the effect of superstructure. A single valueof loading intensity was considered at raft level as 215 KN/m2, whereas line load was considered at level of wallas 385 KN/m. Comparisons were conducted between the various cases and conclusions are made.